Non-Immune Hemolytic Anemia (Hemoglobinopathy) - Ni Putu Yunandari (Jurnal KESANS : Kesehatan dan Sains, 2021)
Hemoglobinopathy is an autosomal recessive disorder that is classified into 2 major groups, namely thalassemia syndromes and structural variants of the hemoglobin chain. Thalassemia is a group of genetic disorders caused by decreased speed of chain synthesis or. The second group, structural abnormalities in the hemoglobin chain, often causes a condition called sickle cell (sickle cell anemia), this structural abnormality occurs due to the substitution of adenine by thymine which causes the conversion of the amino acid glutamate to valine. 7% of the world's population are carriers of hemoglobinopathies. This type of research is literature research or literature review. Based on data from the Indonesian Thalassemia Foundation (YTI) in 2008-2017, 5.8% of thalassemia carriers were found from 12,038 people examined, and 28.62% of 4,137 people according to the results of family screening. thalassemia in 2009-2017. The prognosis of thalassemia disease depends on medication adherence and the type of thalassemia suffered. Death in patients with sickle cell anemia is usually due to co-morbidities such as renal and other organ failure. Early and adequate symptom management can improve the prognosis. This disorder is autosomal recessive which is classified into 2 major groups, namely thalassemia syndrome and structural variants of hemoglobin chains that often produce sickle cell shape